Identification of Ice Plant (Mesembryanthemum crystallinum L.) MicroRNAs Using RNA-Seq and Their Putative Roles in High Salinity Responses in Seedlings - Chiang, Chih-Pin; Yim, Won C.; Sun, Ying-Hsuan; Ohnishi, Miwa; Mimura, Tetsuro; Cushman, John C.; Yen, Hungchen E. (Frontiers in Plant Science, 2016)
The halophyte Mesembryanthemum crystallinum (common or crystalline ice plant) is a useful model for studying molecular mechanisms of salt tolerance. The morphology, physiology, metabolism, and gene expression of ice plant have been studied and large-scale analyses of gene expression profiling have drawn an outline of salt tolerance in ice plant. A rapid root growth to a sudden increase in salinity was observed in ice plant seedlings. Using a fluorescent dye to detect Na+, we found that ice plant roots respond to an increased flux of Na+ by either secreting or storing Na+ in specialized cells. High-throughput sequencing was used to identify small RNA profiles in 3-day-old seedlings treated with or without 200 mM NaCl. In total, 135 conserved miRNAs belonging to 21 families were found. The hairpin precursor of 19 conserved mcr-miRNAs and 12 novel mcr-miRNAs were identified. After 6 h of salt stress, the expression of most mcr-miRNAs showed decreased relative abundance, whereas the expression of their corresponding target genes showed increased mRNA relative abundance. The cognate target genes are involved in a broad range of biological processes: transcription factors that regulate growth and development, enzymes that catalyze miRNA biogenesis for the most conserved mcr-miRNA, and proteins that are involved in ion homeostasis and drought-stress responses for some novel mcr-miRNAs. Analyses of the functions of target genes revealed that cellular processes, including growth and development, metabolism, and ion transport activity are likely to be enhanced in roots under salt stress. The expression of eleven conserved miRNAs and two novel miRNAs were correlated reciprocally with predicted targets within hours after salt stress exposure. Several conserved miRNAs have been known to regulate root elongation, root apical meristem activity, and lateral root formation. Based upon the expression pattern of miRNA and target genes in combination with the observation of Na+ distribution, ice plant likely responds to increased salinity by using Na+ as an osmoticum for cell expansion and guard cell opening. Excessive Na+ could either be secreted through the root epidermis or stored in specialized leaf epidermal cells. These responses are regulated in part at the miRNA-mediated post-transcriptional level.